Estrategias de Marketing para Potenciar los Atractivos Turísticos del cantón Pallatanga provincia de Chimborazo 2018 - Chávez Muñoz, Mónica Estefanía (2019)
The following research´s work called “Marketing Strategies” to boost Pallatanga City´s attractions touristics Province Chimborazo 2018. This proyect has like goal develops Marketing´s Strategies to strengthen whole the tourist places into the town, with the end of improve all tourist`s activitity. Into the reseraching have aimed to design a plan about turistic Marketing which objective is focused in to create new strategies for raising Touristic spaces in Pallatanga City Province Chimborazo. In this way whole will know about Touristic zones that Pallatanga has and so comply our general objective the main axes that support the following strategies: SOCIAL MARKETING, IMAGEN AUDIOVISUAL, BRANDING, MECHANDISING, BTL PUBLICITY, OUTSIDE PUBLICITY AND TOURISM INFORMATION, these strategies will help to get better in many aspects such us: economic, social, environment and cultural. The strategies displayed have been proposed based in the results getting in field´s research for which have interviewed to threes authorities, in this interview could get an deep analysis about the tourism in our town. With these ammunitions have propounded some specific strategies appropiate to the needs the town like are: ADVERSITISING VIDEOS, IDENTIFICATION GRAPH, POP MATERIAL, LED SCREENS, CHARTS INFORMATATION BULLETINS, TOURIST SIGNAGE without aside the necessary budget for it´s development. The methodology applied in the reseraching has been done in different levels like are: Camp, Qualitative and Quantitative, these encompass in specific and general way also here is the publicity and promotion that are always alternatives to give a great service. XX Descriptive terms: Pallatanga, Marketing, Strategies, Marketing Plan Touristic, Attractives´ Places, Performent, Advertising.